Modularity as a key to understanding the system of language processing – cognitive models and their neurological basis - Sadownik, Barbara (Glottodidactica, 2014)
The scope of this paper is the concept of modularity of language, which is a key to understanding the complexity of human cognitive system. The author of the paper presents various arguments in favor of the thesis that both moderate and extreme modularity-related theories allow, too much greater extent than non-modularity theories, for reconstruction and description of complex structures of the language perception and production.